Power and trust as factors influencing tax compliance behavior in Malaysia - Sellywati Mohd Faizal,; Mohd Rizal Palil,; Ruhanita Maelah,; Rosiati Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study adopted the slippery slope framework in the context of tax compliance in Malaysia tax. Thus, the research objective is to examine the effect of slippery slope factors on tax compliance. The slippery slope consists of power and trust. Power is distinguished between legitimate power and coercive power. Power and trust have different influence on tax compliance. Trust is perceived to influence voluntary tax compliance and power influences enforced tax compliance. Survey method is used to collect data involving individual taxpayers as respondents. The findings suggest that only trust has significant effect on tax compliance. Meanwhile, neither legitimate power nor coercive power could influence tax compliance.